Nutritional status of the elderly attending public polyclinics in Benghazi city, Libya - Nouh, Faiza; Omar, Mariam; Younis, Manal; Younis, Moftah (International Journal Of Community Medicine And Public Health, 2017)
Background: Ageing brings various physiological and non physiological changes which influence the nutritional status. Methods: A cross-sectional study extended from 1st December 2007 to 15th April 2008 on elderly of both sexes attending public polyclinics in Benghazi city. Results: 6.5% was the prevalence of malnutrition. 36.8% was the percentage of elderly at risk of malnutrition. Age, sex, occupation, income inadequacy to food, oral problems, dysphagia, constipation and dehydration, activity level, chronic disease, food intolerances and BMI all these factors were the various physiological and non-physiological factors associated with the nutritional status of the subjects. Conclusions: Outpatients elderly in Benghazi should be routinely screened and assessed if needed, for malnutrition or its risk.